Age matters: differences in exercise-induced cardiovascular remodelling in young and middle aged healthy sedentary individuals. (1st June 2020) - Torlasco, Camilla; D'Silva, Andrew; Bhuva, Anish N; Faini, Andrea; Augusto, Joao B; Knott, Kristopher D; Benedetti, Giulia; Jones, Siana; Zalen, Jet Van; Scully, Paul; Lobascio, Ilaria; Parati, Gianfranco; et al.
Abstract: Aims: Remodelling of the cardiovascular system (including heart and vasculature) is a dynamic process influenced by multiple physiological and pathological factors. We sought to understand whether remodelling in response to a stimulus, exercise training, altered with healthy ageing. Methods: A total of 237 untrained healthy male and female subjects volunteering for their first time marathon were recruited. At baseline and after 6 months of unsupervised training, race completers underwent tests including 1.5T cardiac magnetic resonance, brachial and non-invasive central blood pressure assessment. For analysis, runners were divided by age into under or over 35 years (U35, O35). Results: Injury and completion rates were similar among the groups; 138 runners (U35: n = 71, women 49%; O35: n = 67, women 51%) completed the race. On average, U35 were faster by 37 minutes (12%). Training induced a small increase in left ventricular mass in both groups (3 g/m 2, P < 0.001), but U35 also increased ventricular cavity sizes (left ventricular end-diastolic volume (EDV)i +3%; left ventricular end-systolic volume (ESV)i +8%; right ventricular end-diastolic volume (EDV)i +4%; right ventricular end-systolic volume (ESV)i +5%; P < 0.01 for all). Systemic aortic compliance fell in the whole sample by 7% ( P = 0.020) and, especially in O35, also systemic vascular resistance (–4% in the whole sample, P = 0.04) and blood pressure (systolic/diastolic, whole sample: brachial –4/–3 mmHg, central –4/–2 mmHg, all P < 0.001; O35: brachial –6/–3 mmHg, central –6/–4 mmHg, all P < 0.001). Conclusion: Medium-term, unsupervised physical training in healthy sedentary individuals induces measurable remodelling of both heart and vasculature. This amount is age dependent, with predominant cardiac remodelling when younger and predominantly vascular remodelling when older.